Murillo Orellana,Diego Djorkaeff(2023)EFECTO DE DOS ENMIENDAS AGRICOLAS AL SUELO EN CULTIVO BANANO (Musa paradisiaca L.) VARIEDAD WILLIAMS, EN EL CANTÓN BUENA FE.Quevedo.UTEQ.68p. - Murillo Orellana , Diego Djorkaeff (2023)
In the Buena Fe canton, province of Los Ríos, the present research was carried out with the objectives of evaluating two types of agricultural amendments based on lime on the quality of the soil in the Williams variety banana crop, measuring the effect of agricultural amendments and establishing the changes in the soil due to the effect of the amendments applied, the treatments were: T1 Without amendments, T2 Dolomite lime 1. 5 t ha-1 (100 mesh), T3 Biocal (liquid lime in suspension) 10 liters ha-1 (250 mesh) and T4 Dolomite lime 0.75 t ha-1 (100 mesh) + Biocal (liquid lime in suspension) 5 liters ha-1 (250 mesh) arranged in a randomized complete block design with 3 replications. Tukey's test (p≤ 0.05) was used to compare treatment averages. The variables studied were: number of leaves, stem diameter, height of the son and pH and electrical conductivity of the soil, the treatments had a positive influence on the responses of the soil modifying the pH and electrical conductivity also had a positive influence on the agronomic responses of the plant, within the results achieved, the T3 treatment presents more height and number of leaves of the son, the T4 treatment presents greater perimeter of the stem in all the evaluations. In soil pH values, treatment T2 stands out in all evaluations. In terms of soil electrical conductivity (mS/cm), treatment T2 had the highest conductivity values in relation to the other treatments evaluated.